2015
DOI: 10.1016/j.envres.2015.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Lead concentrations in whole blood, serum, saliva and house dust in samples collected at two time points (12 months apart) in Santo Amaro, BA, Brazil

Abstract: Results support the validity of lead determination in blood and in house dust to assess lead exposure over time. However, lead in blood and lead in dust did not correlate with lead in serum or lead in saliva.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The levels of exposure in this study were similar to what have been shown in studies conducted in Santo Amaro Ba, Brazil, where two samples were collected over 12 months. At the first time point the level of Pb in serum was 0.01-1.82 µg/L while one year later there was a reduction in levels of Pb in serum to 0.04-0.66, consistent with reduction of Pb in the environment in this city (de Souza Guerra et al, 2015). Serum is considered to be a good biomarker for Pb exposure and some studies report a high degree of correlation between serum and whole blood levels (Hernández-Avila et al, 1998;Rezende et al, 2010).…”
Section: Discussionmentioning
confidence: 65%
“…The levels of exposure in this study were similar to what have been shown in studies conducted in Santo Amaro Ba, Brazil, where two samples were collected over 12 months. At the first time point the level of Pb in serum was 0.01-1.82 µg/L while one year later there was a reduction in levels of Pb in serum to 0.04-0.66, consistent with reduction of Pb in the environment in this city (de Souza Guerra et al, 2015). Serum is considered to be a good biomarker for Pb exposure and some studies report a high degree of correlation between serum and whole blood levels (Hernández-Avila et al, 1998;Rezende et al, 2010).…”
Section: Discussionmentioning
confidence: 65%